'The Collective Biography of Archaeology in the Pacific': Seven Years of the CBAP Project - Matthew Spriggs (Bulletin of the History of Archaeology, 2023)
The Australian Research Council (ARC) Laureate Project, The Collective Biography of Archaeology in the Pacific or ‘CBAP’ was funded between 2015-2020 and, due to COVID disruptions, associated events continued until the end of 2022. Some of the initial aims included: to create a sub-field of the history of Pacific archaeology; to re-define the development of Australian archaeology within its wider Oceanic context; to re-discover the contribution of both French and German scholars; to recover the considerable amount of archaeological excavation that took place in the Pacific from the 1870s until WWII; to re-conceptualise the perennial issue of trans-Oceanic cultural contacts; to redress the neglect of the role of Indigenous Pacific scholars and of women in archaeology; and to re-engage with descendant communities in the light of our research and its findings. The paper discusses the project’s results in light of these and other emerging aims during the last seven years. It also provides a comprehensive bibliography of publications by the Project’s main contributors.